Continuing professional development of vocational teachers in Kenya: Motivations, practices and teacher profiles - Moses Njenga (International Journal of Educational Research Open, 2023)
Purpose: Despite the important role that motivation plays in the Continuing Professional Development (CPD) of teachers, it is not always clear what motives guide vocational teachers in their CPD. This study therefore investigated the motives vocational teachers have for participating in CPD and how those motives influence their CPD practices. Methods: The study adopted a qualitative approach, wherein data collected using semi-structured interviews with vocational teachers was inductively coded to identify how motives influence CPD practices. Vocational teachers were viewed as adult learners while motivation was conceptualized as dynamic and contingent upon an individual's context. Findings: Vocational teachers in Kenya were found to engage in both formal and informal CPD guided by different motives. Four distinct categories of motives were identified related to the search for performance competence, status and authority, relief from routine, and compliance with requirements. Further analysis revealed four motivational orientations characterized by underlying motives, their associated CPD practices, and teacher profiles. Value: The resulting characterization of motives, practices, and teacher profiles enables prediction and empirical verification of which vocational teachers are likely to adopt a particular learning method and what content they are likely to focus on. Further empirical verification is called for.